2018
DOI: 10.1111/dech.12461
|View full text |Cite
|
Sign up to set email alerts
|

Employment Change in Occupations in Urban India: Implications for Wage Inequality

Abstract: This article analyses employment and wage change patterns in India for a period spanning almost three decades, from 1983–84 to 2011–12. Using data from the National Sample Survey Organization, the study finds evidence of job polarization (employment growth in low‐ and high‐skill jobs and decline in middle‐skill jobs) in urban India during the 1990s and 2000s, and employment upgrading in the 1980s. Consistent with the literature on job polarization, the article finds a reduction in employment share in routine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
1
15
0
2
Order By: Relevance
“…The study by Vashisht and Dubey (2018) concur with the findings of Sarkar (2017). They argue that the relative demand for non-routine cognitive tasks has increased four times since 1998 than in the period before.…”
Section: Supply-side Factorssupporting
confidence: 74%
See 3 more Smart Citations
“…The study by Vashisht and Dubey (2018) concur with the findings of Sarkar (2017). They argue that the relative demand for non-routine cognitive tasks has increased four times since 1998 than in the period before.…”
Section: Supply-side Factorssupporting
confidence: 74%
“…Second, whilst analysing the trend of real daily wage for each decile of workers, Sarkar (2017) found that the value for the highest (10 th decile) and the lowest (90 th decile) showed a sharp monotone increase whilst that of the median (50 th decile) showed a decline, especially after 1999. Growth of average earnings for occupational quintiles during the same period sheds light on wage disparities as shown in Figure 7.…”
Section: Persistence Of Routine Occupationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The evolution of earnings inequality in India has been examined by Kijima (2006) and Chamarbagwala (2006), and later by Azam (2012). A study by Sarkar (2019) looks at changes in earnings inequality under the lens of a changing occupational structure in India up to 2011. She concludes that earnings inequality has been increasing in India and, to some extent, this can be explained by employment and wage polarization in the country.…”
Section: Introductionmentioning
confidence: 99%